Law Enforcement Officials’ Opinion on the Security Situation and Cooperation on the Danube: – Based on the “DARIF 2022” International Questionnaire Survey - Kalmár, Ádám (Magyar Rendészet, 2023)
The aim of the study is to analyse the bilateral and multilateral law enforcement cooperation between the Danube Member States and the relevant international stakeholders. A key issue for the security of the European Union and the Schengen area is the joint strengthening of the security of the Danube river. In the most important transnational maritime areas (Black Sea, Baltic Sea), there is a regulation based on the operation of a common centre for law enforcement coordination, which allows a rapid and efficient exchange of information between the Member States in order to combat organised crime. The Danube is one of Europe’s most important waterways, but the absence of a multilateral international agreement on the cooperation and coordination signed by all the Member States to ensure continuous cooperation and exchange of information is believed to have a negative impact on border security. The research was carried out by an online questionnaire survey among 201 persons in staff from the participating organisations of 10 Danube Member States during the DARIF joint operation, which was conducted from 12–16 September 2022 and extended until 30 September 2022. The questionnaire was prepared in Hungarian, English, and in German, Slovak, Croatian, Serbian, Romanian, Bulgarian and Ukrainian languages, to encourage respondents to participate in the survey. The questionnaire survey among the Danube law enforcement agencies confirmed that the lack of a permanent Law Enforcement Coordination Centre and Cooperation Forum is a significant security deficit in the countries of the Danube Region. The creation of a network of national contact points specialising in international information exchange on the Danube is necessary; it is not sufficient to make better use of the existing network of direct information exchange channels (e.g. Police and Customs Cooperation Centres).